The Dynamics Of Cohabitation Regulation In The National Criminal Code And Its Implications For Raid Operations By The Pamong Praja Police Unit (Satpol Pp) - Mu’tia Qiqi Fatwa Auliyana; Rahadi Wasi Bintoro (UNIVERSITAS PAKUAN, 2026)
The ratification of Law Number 1 of 2023 concerning the Criminal Code (KUHP) brings significant updates in the regulation of moral norms, especially related to cohabitation, which is categorized as an absolute complaint offense. This arrangement is at the intersection between the interests of public order and the protection of private space, especially in the enforcement practice by the Pamong Praja Police Unit (Satpol PP) which has been conducting raids or raids based on Regional Regulations (Perda). This study aims to analyze the influence of cohabitation regulations in the National Criminal Code on the limits of the authority of Satpol PP and examine its impact on the practice of raids in private spaces. The research method used is normative juridical with a legislative and conceptual approach, based on literature studies on secondary data in the form of primary, secondary, and tertiary legal materials. The results of the study show that Article 412 of the Criminal Code only limits the enforcement of cohabitation crimes which can only be carried out on the basis of complaints from parties who have legal rights, so that Satpol PP does not have the authority to conduct raids or enter private spaces without complaints and without valid legal procedures. The practice of raids based on the Regional Regulation has the potential to be contrary to the principles of legality, protection of privacy, and human rights principles. The conclusion of the study emphasizes the need to adjust regional regulations and change the enforcement paradigm from moral policing to the due process of law. It is recommended to harmonize the new Criminal Code with the Regional Regulation, the preparation of technical guidelines for Satpol PP, as well as socialization for the apparatus and the public, supported by further empirical research to assess the application of rules in the field.